Student mobility in low quality schools: segmentation among the most vulnerable students - Román, Marcela; Perticará, Marcela (Estudios de Economía, 2012)
This study addresses the phenomenon of permanence for long years of low performance (urban) schools, measured by SIMCE. We also analyze mobility of students to other schools of same or better quality. The results show that student´s mobility rates in these schools is almost 11%. Almost 30% of the students who change schools go to a school of the same or worse quality. Students with greater probabilities of changing to better performance (higher quality) schools are those pertaining to groups with greater economic resources and cultural capital or better academic performance, which could account for strong segmentation that exists in the Chilean educational system.